Pembinaan Nilai-nilai Kejujuran Menurut Rasulullah Saw - Madani, Hanipatudiniah (Fakultas Ushuluddin UIN Sunan Gunung Djati Bandung, 2021)
This study aims to discuss the hadith about honesty and it guidance. This research method is qualitative with a literature study approach and content analysis. The results and discussion of this study include general views on honesty, hadith about honesty, and fostering honesty values according to the Messenger of Allah. The conclusion of the study shows that honesty is being in accordance with the reality of truth. Islam recommends to its people to always be honest, because honesty is the source of goodness in this world and in the hereafter. So, honesty is an important trait to be instilled in humans.